3ΛH and 3ΛH production in Pb-Pb collisions at √sNN=2.76 TeV - Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aimo, I.; Aiola, S.; Ajaz, M.; Akindinov, A.; et al. (Elsevier, 2016)
The production of the hypertriton nuclei 3H and 3¯ H has been measured for the first time in Pb–Pb collisions at √sNN = 2.76 TeV with the ALICE experiment at LHC. The pT-integrated 3 H yield in one unity of rapidity, dN/dy × B.R. 3 H→3He,π− = (3.86 ± 0.77(stat.) ± 0.68(syst.)) × 10−5 in the 0–10% most central collisions, is consistent with the predictions from a statistical thermal model using the same temperature as for the light hadrons. The coalescence parameter B3 shows a dependence on the transverse momentum, similar to the B2 of deuterons and the B3 of 3He nuclei. The ratio of yields S3 = 3 H/(3He×/p) was measured to be S3 = 0.60±0.13(stat.)±0.21(syst.) in 0–10% centrality events; this value is compared to different theoretical models. The measured S3 is compatible with thermal model predictions. The measured 3 H lifetime, τ = 181+54 −39(stat.) ± 33(syst.) ps is in agreement within 1σ with the world average value.
Keywords: Hypertriton nuclei; Pb–Pb collisions; Coalescence parameter; Transverse momentum; https://purl.org/pe-repo/ocde/ford#1.03.04